STATUS KEBERSIHAN MULUT DAN KESEHATAN GINGIVADI DAERAH TERTINGGAL(Kajian pada Siswa SMP Muhammadiyah 1 Pundong Desa SeloharjoKecamatan Pundong Kabupaten Bantul) - , NORANITA EVI SETIYA WERDANI, drg. Prayitno, SU. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The condition of a rural recidence can affect childâs oral hygiene and gingival health status. This is affected by some risk factors such as brushing teeth behaviour, social economy, dental visit and the difference of living place. This study aimed to find out the picture of oral hygiene and gingival health status in a left behind area in the student of SMP Muhammadiyah 1 Pundong. This study was a descriptive survey with a total of 210 subjects. This Study was analyzed by a bar diagram frequency distribution and presented descriptively. The result of this study showed that oral hygiene and gingival health status in a rural recidence had the highest percentage in a moderate category (48,6%) while the ones with mild gingivitis had a percentage of (56,2%). This study was can concluded that the majority of SMP Muhammadiyah 1 Pundong experience oral hygiene moderate category and mild gingivitis, necessary preventive oral health to prevent disease progression.